The Effectiveness Of Using Corsets On Reducing Pain Scale In Post SC Patients At Eka Hospital, South Tangerang In 2022 - Akiria Santi, Amy; Sukarni, Sukarni (International Journal of Health and Pharmaceutical (IJHP), 2023)
The use of a corset is something that is done by post partum mothers both in normal delivery and sectio caesarea, where the corset can help the process of uterine involution and in post SC delivery can help reduce pain when mobilizing. To determine the Effectiveness of Using Corsets on Reducing Pain Scale in Post SC Patients. Research Methods: This research was experimental (quasi-experimental) with The Nonrandomized Control Group Pretest Posttest Design with a quantitative approach. In this study, it was divided into 2 groups: the control group did not use corsets while the intervention group used corsets. After that the researchers assessed the decrease in pain scale in post SC patients. The number of samples was 20 people. It is known that the average value of the statistical test results obtained a p value = 0.000 (<α 0.05), meaning that there is an Effectiveness of Using Corsets on Reducing Pain Scale in Post SC Patients at Eka Hospital, South Tangerang in 2022. Advice to health workers to be able to provide health education or information. to patient about wearing a corset as non farmacologic methode to reduce post caecarea pain.